One step synthesis of indirubins by reductive coupling of isatins with KBH4. Issue 19 (11th May 2017) - Wang, Cuiling; Yan, Jiaxu; Du, Mo; Burlison, Joseph A.; Li, Chi; Sun, Yanni; Zhao, Danqing; Liu, Jianli
Abstract: One step synthesis of the natural product indirubin by reductive coupling of isatin with KBH4 is described and a possible mechanism for the reaction is proposed. Eleven indirubin derivatives were obtained easily from the corresponding substituted isatin. Graphical abstract: